The Ordinary Looks behind the Horrifying Screams: The Secrecies of Border Spirits in 20th Century Finnish Belief Narratives - Kari Korolainen (Humanities, 2024)
This paper discusses the secrecies of border spirits within 20th century Finnish belief narratives. The aim is to explore how and in which contexts the imaginary aspects of border spirit narratives link to the idea of the “power of storytelling”. The following study touches on areas such as the suspension of the fantasy and sociopolitical aspects within the narratives. The folklore materials focus mainly on the Finnish heartland and partly on the national borders. Especially, narrative research methods were used to analyse what is heard and seen of the border spirits and what contexts these narratives involve. Moreover, the results touch on the dynamics of belief narratives without limiting them to the territorial aspects of borders. Hence, the study also explores interpretative bridges between folklore and border studies.